The Genetic Architecture of Bovine Telomere Length in Early Life and Association With Animal Fitness - Ilska-Warner, Joanna J.; Psifidi, Androniki; Seeker, Luise A.; Wilbourn, Rachael V.; Underwood, Sarah L.; Fairlie, Jennifer; Whitelaw, Bruce; Nussey, Daniel H.; Coffey, Mike P.; Banos, Georgios (Frontiers in Genetics, 2019)
Health and survival are key goals for selective breeding in farm animals. Progress, however, is often limited by the low heritability of these animal fitness traits in addition to measurement difficulties. In this respect, relevant early-life biomarkers may be useful for breeding purposes. Telomere length (TL), measured in leukocytes, is a good candidate biomarker since TL has been associated with health, ageing and stress in humans and other species. However, telomere studies are very limited in farm animals. Here we examined the genetic background, genomic architecture and factors affecting bovine TL measurements in early life, and the association of the latter with animal fitness traits expressed later in life associated with survival, longevity, health and reproduction. We studied two TL measurements, one at birth (TLB) and another during the first lactation (TLFL) of a cow. We performed a genome-wide association study of dairy cattle TL, the first in a non-human species, and found that TLB and TLFL are complex, polygenic, moderately heritable and highly correlated traits. However, genomic associations with distinct chromosomal regions were identified for the two traits suggesting that their genomic architecture is not identical. This is reflected in changes in TL throughout an individual’s life. TLB had a significant association with survival, length of productive life and future health status of the animal, and could be potentially used as an early-life biomarker for disease predisposition and longevity in dairy cattle.